LABOR PRODUCTIVITY IN UZBEKISTAN: CHALLENGES AND OPPORTUNITIES (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article examines Uzbekistan's labor productivity, highlighting major issues and areas for development. The report makes recommendations for methods to increase labor productivity while highlighting structural issues and economic reforms. The findings demonstrate the potential significance of focused policies, technology advancements, and educational changes in guaranteeing long-term productivity development. These strategies will raise worker skill levels and aid in modernizing the Uzbekistan’s economy. The report also emphasizes the necessity of developing fresh avenues for social progress and economic expansion. Through these procedures, Uzbekistan will be able to improve its standing in international competitiveness.
Keywords: labor productivity, economic growth, economic reforms, innovation